Investigation of Nano Spray-Dried, Hyaluronic Acid-Modified Polymeric Micelles for Nasal Administration - Bence Sipos; Levente Mayer; Mária Budai-Szűcs; Gábor Katona; Rita Ambrus; Ildikó Csóka (Pharmaceutics)
Background/Objectives: The combination of nanomedicine with nasal administration is of paramount importance in current research and development. Polymeric micelles coated with hyaluronic acid may be a suitable solution to enhance drug release and permeation whilst properly adhering to the nasal mucosa, increasing residence time. Methods: Solid state characterization included morphology and laser diffraction-based size analysis and X-ray powder diffraction. The characterization of dispersed polymeric micelles in aqueous media was performed based on dynamic light scattering and determining the solubility enhancement related factors such as encapsulation efficiency and thermodynamic solubility. In vitro nasal drug release and permeability studies were also conducted to characterize the different hyaluronic acid-modified polymeric micelles. Quantitative measurements were carried out via liquid chromatography. Results: Concentration dependence on hyaluronic acid was found during all measurements, with one formulation candidate overcoming the others. With a high yield above 80%, monodispersed particles were formulated with an approximately 4 µm particle size in uniform distribution and spherical morphology. The small micelle size (107.3 nm) in uniform manner led to a high encapsulation efficiency above 80% and released the drug amount above 70% in 15 min. High drug permeation was also achieved compared with the initial active substance by itself. Conclusions: A value-added polymeric micelle formulation was developed with rapid drug release and permeation kinetics alongside its high mucoadhesion.